PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS GENU SINISTRA DENGAN MODALITAS MWD ,LASER DAN QUADRICEPS SETTING DI RSUD CIKALONG WETAN KABUPATEN BANDUNG BARAT - Aldis Gian Rosandi; Ika Rahman (Journal of Health Science and Physiotherapy, 2021)
Osteoarthritis Genu is a disease that affects the knee joint. This studydetermine the implementation of Physiotherapy in reducing pain and increasing LGS to increase the strength of themuscle aimsOsteoarthritis Genu Sinistra towith the modalities of MWD, Laser and Quadriceps Setting 1. From the results obtained after therapy for 6 times, the results of the assessment of knee pain were silent pain T1=0 to T6=0 tenderness T1=3 to T6=1 motion pain T1=5 to T6=3. Increased muscle strength T1=4 to T6=5. As well as an increase in passive Genu Sinistra Osteoarthritis LGS, namely T1 = S 00-00-1200 to T6 = S 00-00-1300 and active Genu Sinistra Osteoarthritis LGS, namely T1 = S 00-00-1150 to T6 = S 00-00-1250.